LAYANAN PEMINATAN PADA KURIKULUM MERDEKA - Cahyono, Tri (Jurnal Bimbingan dan Konseling Borneo, 2022)
Abstract Student specialization is a process of making choices and decisions by students in areas of expertise based on understanding their own potential and existing opportunities. Service specialization of students is the responsibility of the principal by involving all components in the school. Specialization in cross-subject options and the choice of deepening subject matter is an effort to assist students in choosing and determining the subjects to be followed in high school education units in order to understand and choose the direction of career development, and prepare themselves and choose further education up to university. according to general basic abilities, talents, interests and preferences of each student. This research is library research that examines the process of specialization services at the senior high school (SMA) level in the independent curriculum. The results of this study concluded that specialization services at the SM School level were carried out through 4 stages, including: 1) providing information on specializations; 2) data collection; 3) identification and determination of specialization; 3) adjustment and assistance; 4) monitoring and follow-up. Keywords: merdeka’s curriculum, specialization services AbstrakPeminatan peserta didik merupakan suatu proses pengambilan pilihan dan keputusan oleh peserta didik dalam bidang keahlian yang didasarkan atas pemahaman potensi diri dan peluang yang ada. Pelayanan peminatan peserta didik menjadi tanggung jawab kepala sekolah dengan melibatkan semua komponen yang ada di sekolah. Peminatan pilihan lintas mata pelajaran dan pilihan pendalaman materi mata pelajaran merupakan upaya untuk membantu peserta didik dalam memilih dan menetapkan mata pelajaran yang diikuti pada satuan pendidikan di SMA dalam rangka memahami dan memilih arah pengembangan karir, dan menyiapkan diri serta memilih pendidikan lanjutan sampai ke perguruan tinggi sesuai dengan kemampuan dasar umum, bakat, minat dan kecenderungan pilihan masing-masing peserta didik. Penelitian ini adalah penelitian Pustaka yang mengkaji proses layanan peminatan pada jenjang Sekolah Menengah Atas (SMA) di kurikulum merdeka. Hasil kajian ini menyimpulkan bahwa layanan peminatan pada jenjang Sekolah SM)dilakukan melalui 4 tahapan, diantaranya: 1) pemberian informasi peminatan; 2) pengumpulan data; 3) identifikasi dan penetapan peminatan; 3) penyesuaian dan pendampingan; 4) monitoring dan tindak lanjut.  Kata Kunci : Kurikulum merdeka, layanan peminatan